Design a wristband based on Internet of Things for blind people - Atika Juliadrianni; Ibnu Ziad; Suroso Suroso (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
This research aims to design a tool for blind people and facilitate activities for blind people in the form of wristbands based on the Internet of Things (IoT). This research uses experimental methods from quantitative methodology with a Pre-Experimental design. This tool will help provide information to the wristband user to avoid obstacles. This tool will help provide information to the wristband user to avoid obstacles. This wristband is designed using the ultrasonic sensor HC-SRF05 which will be processed in the NodeMCU ESP8266 microcontroller as input, with a buzzer as output.  This wristband is equipped with GPS for monitoring the whereabouts of wristband users. This tool can detect objects in front with a radius of approximately 100 cm to provide information to users to avoid obstacles.